1977
DOI: 10.3758/bf03209200
|View full text |Cite
|
Sign up to set email alerts
|

Prior context and the perception of lexically ambiguous sentences

Abstract: The perceptual complexity of lexically ambiguous and unambiguous sentences was compared in three experiments. In Experiment 1, the report of ambiguous words from rapidly presented ambiguous sentences was worse than the report of corresponding unambiguous words from unambiguous sentences. Results of Experiment 2 showed that the effect was not reduced by the presence of prior biasing context within the sentence. Experiment 3 repeated the finding with a sentence meaning classification task. It was concluded that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0
1

Year Published

1980
1980
1992
1992

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 25 publications
2
12
0
1
Order By: Relevance
“…The present data, then, seem critical to support of the exhaustive access position; to accept this theory and rule out the serial self-terminating access model, it was necessary to establish evidence that a low-frequency meaning for an ambiguity is accessed, even in the presence of biasing context that is compatible with the high-frequency meaning for that ambiguity. As argued previously, it appears likely that the Hogaboam and Perfetti results are a function of the use of a technique Finally, the present experiments also provide confirmation of the somewhat more indirect support given to the exhaustive access model by Cairns and Hsu (1980), Holmes et al (1977), Lackner and Garrett (1972), SWinney (1979), andTanenhaus et al (1979).2 Further, the results of the examination of the time course of lexical meaning activation provide verification of a number of additional facts that have been posited concerning the lexical processing system. In summary, lexical access appears to be an exhaustive and autonomous subroutine of the sentence comprehension process (autonomous in the sense that it does not appear to be driven or guided by previously occurring semantic information).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The present data, then, seem critical to support of the exhaustive access position; to accept this theory and rule out the serial self-terminating access model, it was necessary to establish evidence that a low-frequency meaning for an ambiguity is accessed, even in the presence of biasing context that is compatible with the high-frequency meaning for that ambiguity. As argued previously, it appears likely that the Hogaboam and Perfetti results are a function of the use of a technique Finally, the present experiments also provide confirmation of the somewhat more indirect support given to the exhaustive access model by Cairns and Hsu (1980), Holmes et al (1977), Lackner and Garrett (1972), SWinney (1979), andTanenhaus et al (1979).2 Further, the results of the examination of the time course of lexical meaning activation provide verification of a number of additional facts that have been posited concerning the lexical processing system. In summary, lexical access appears to be an exhaustive and autonomous subroutine of the sentence comprehension process (autonomous in the sense that it does not appear to be driven or guided by previously occurring semantic information).…”
Section: Discussionsupporting
confidence: 76%
“…From this, it was concluded that both meanings of the ambiguity were accessed, at least momentarily, thus providing the facilitation for lexical decisions to words related to each of those meanings. In other recent work, Holmes, Arwas, and Garrett (1977) have shown that time to classify an unbiased sentence as meaningful is increased by the presence of a lexical ambiguity and that the number of words correctly recalled under the rapid serial visual presentation technique is, likewise, smaller in the presence of an ambiguity (Chodorow, 1979, has found a similar result in the auditory domain). Cairns and Hsu (1980) have also recently supported this contention using a phoneme monitoring technique (as have HolleyWilcox & Blank, 1980, in nonsententiallexical decision experiments) .…”
supporting
confidence: 56%
See 1 more Smart Citation
“…The modular view holds that all meanings of the word are initially accessed, since the lexical access mechanism can't "know" what the context requires, and all meanings are then passed to the integration level, where context selects the proper one (the Post Decision Hypothesis). Early research produced mixed results, some studies supporting one hypothesis, some the other (Conrad, 1974;Foss and Jenkins, 1973;Holmes, 1977;Lackner andGarret, 1972: Swinney andHakes, 1976). However, most of these studies only looked at one time point of the process, which as later results show, explains the discrepancy.…”
Section: Lexical Accessmentioning
confidence: 99%
“…A major issue addressed in previous research has been whether lexical access to alternative meanings of ambiguous words is context-dependent or initially exhaustive, with context operating on "postaccess" processes. Past cross-modal studies, however, may have failed to adequately control the polarity of ambiguous items (i.e., the degree to which one word sense dominated over the other) and the relatedness of the ambiguous items to the lexical targets (Holmes, Arwas, & Garrett, 1977;Onifer & Swinney, 1981;Seidenberg, Tanenhaus, Leiman, & Bienkowski, 1982;Swinney, 1979; Tabossi, 1988; Tabossi, Colombo, & Job, 1987; Tanenhaus, Leiman, & Seidenberg, 1979).…”
mentioning
confidence: 99%